Correlations between forest soil quality and aboveground vegetation characteristics in Hunan Province, China - Shen, Yafei; Li, Jing; Chen, Fangfang; Cheng, Ruimei; Xiao, Wenfa; Wu, Lichao; Zeng, Lixiong (Frontiers in Plant Science, 2022)
As a key component of terrestrial ecosystems, soil interacts directly with aboveground vegetation. Evaluating soil quality is therefore of great significance to comprehensively explore the interaction mechanism of this association. The purpose of this study was to fully understand the characteristics of aboveground vegetation, soil quality, and their potential coupling relationship among different forest types in Hunan Province, and to provide theoretical basis for further exploring the mechanisms underlying soil–vegetation interactions in central China. We have set up sample plots of 5 kinds of forests (including broad-leaved forest, coniferous forest, coniferous broad-leaved mixed forest, bamboo forest and shrub forest) in Hunan Province. Based on this, we used variance analysis, principal component analysis and regression analysis to explore the differences of vegetation characteristics and soil physical and chemical properties among the five stand types. Finally, we explored the coupling relationship between soil quality and aboveground vegetation characteristics of each forest. We found that the vegetation distribution of the five forest types in subtropical Hunan Province is the result of their preferences on different habitat in the climate zone. There were significant differences in soil quality among the forest types, ranked as follows: shrub forest > bamboo forest > broad-leaved forest > mixed forest. There was a negative correlation between vegetation richness and soil quality in broad-leaved forest and shrub forest, but a positive correlation between vegetation and soil quality in forest land with weak competition. The competitive advantage of shrubs was still suppressed by strong dominant trees. As a necessary habitat condition for aboveground vegetation, soil directly determines the survival and prosperity of species. The nutrient return of fallen vegetation can also supplement the consumption of soil quality, thus enhancing the chances of vegetation survival. Under the strong competitive environment, vegetation soil shows as one aspect wanes, the other waxes. However, in a weak competitive environment, the relationship between vegetation and soil is mild and promoted each